Phase stability, fuel properties, and diesel engine performance of palm‐oil‐based microemulsion biofuels - Chodchanok Attaphong; Nattaya Morawan; Piampoom Sarikprueck; Ampira Charoensaeng; Sutha Khaodhiar (Journal of Surfactants and Detergents, 2023)
Abstract Microemulsification and blending are two viscosity‐modifying techniques of vegetable oils for direct use with diesel engine. In this study, alcohol blends are mixtures of ethanol, diesel, and palm‐oil biodiesel while microemulsion biofuels are thermodynamically stable, clear, and single‐phase mixtures of diesel, palm oil, and ethanol stabilized by surfactants and cosurfactants. Although there are many studies on biofuels lately, there is limited research on using biodiesel as a surfactant in microemulsion formulations and applied on engine performance at different engine loads. Therefore, the objectives are to investigate phase stability and fuel properties of formulated biofuels (various blends and microemulsions), to determine the engine performance at different engine loads (no load, and from 0.5 to 2.0 kW), and to estimate laboratory‐scale cost of the selected biofuels compared to diesel and biodiesel. The results showed that phase stability and fuel properties of selected microemulsion biofuels are comparable to diesel and biodiesel. These microemulsion biofuels can be applied to the diesel engine at different loads while diesel‐ethanol blends and palm‐oil‐biodiesel‐ethanol blends cannot be. It was found that the energy efficiencies of the system using microemulsion biofuels were slightly lower than the average energy efficiency of diesel engine. From this study, it can be summarized that microemulsion biofuels can be formulated using palm‐oil biodiesel (palm‐oil methyl ester) as a bio‐based surfactant and they can be considered as environmentally‐friendly alternatives to diesel and biodiesel. However, cost considerations showed that the raw materials should be locally available to reduce additional costs of microemulsion biofuels.
Keywords: Biodiesel Production and Applications; Lubricants and Their Additives; Advanced Combustion Engine Technologies